MOTIVASI INGGRIS MENDUKUNG REFERENDUM DALAM PENYELESAIAN KONFLIK PEREBUTAN KEPULAUAN FALKLAND - Brian Rifqi Andinata; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This is a Diplomatic study in International Relations which describes about the reason behind Britain’s support to the Falkland Islands Referendum. The Falkland Islands sovereignity disputes happened between The Great Britain and Argentina. The Falkland Islanders and Great Britain think that Referendum is the right way of showing the world their opinion about the Sovereignity on the falkland Islands. This research is expected to give comprehension about Great Britains motivation in their support on the Falkland Islands Referendum.This is Qualitative research which used descriptive methods, and collecting data from books, journals, official publications and relevant websites. This paper used the reallist perspective and Security theory proposed by Barry Buzan.The result of this research shows that the motivation behind the Britain Support on the Falkland Islands referendum is to Respect the Falkland Islanders opinion about the sovereignity over their homeland and protecting their Sovereingity on the Falkland islands and doing their duty or responsibility on the Falkland Island International Affairs and also Maintaining the Islands as their Overseas Teritory.Key Words: Great Britain, Argentina, Referendum, Sovereignity